Pembelajaran Al Islam ( Akhlak ) dengan Menggunakan Media Canva di SMA Muhammadiyah 3 Jember - Romelah Romelah; Nur Dzaedzatul H (Moral : Jurnal kajian Pendidikan Islam, 2025)
, This research aims to describe the development of Al-Islam (Akhlak) learning using Canva media at SMA Muhammadiyah 3 Jember. This research approach uses qualitative case study type, located at SMA Muhammadiyah 3 Jember, with informants consisting of Al Islam teachers and class X students. Data collection techniques use observation, interviews and documentation. Meanwhile, the validity of the data uses data source triangulation techniques and for data analysis in this research several techniques are used, including observation, interviews and documentation using Miller Hubman and Saldana theories. Steps for collecting data through surveys to draw valid conclusions. The results of this research show that Al-Islam (Akhlak) learning using Canva media is very good to be implemented at SMA Muhammadiyah 3 Jember